Integration of Ethnomathematics in Science, Technology, Engineering, and Mathematics Learning to Improve Students' Science and Technology Literacy: Integrasi Etnomatematika dalam Pembelajaran STEM Untuk Meningkatkan Literasi Sains dan Teknologi Siswa - Alvian M. Sroyer; Henderina Morin; Agustinus Languwuyo; Ishak Beno; Abraham; Radian Situmeang (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The implementation of Science, Technology, Engineering, and Mathematics (STEM) learning in many remote schools, including SMP Negeri Depapre, Jayapura Regency, is sub-optimal and lacks relevance to the students' local cultural context. This results in low motivation and difficulties for students in understanding abstract concepts. This community service program aimed to develop and implement an Ethnomathematics-based STEM learning model that links science and mathematical concepts with local Papuan cultural practices, such as geometric patterns in carvings, counting systems, or physics principles in fishing tools. The methods included module development, teacher training (workshop), and learning implementation using a Project-Based Learning (PjBL) approach involving 18 seventh-grade students and 7 assisting teachers. Activities involved measuring cultural objects (like Tumoko Batu) and creating cultural products (like the Papuan Flute and Sentani Drum). The results showed a significant change, with students becoming more enthusiastic and active in discussions. Quantitatively, there was an average increase in conceptual understanding of 42.25% following the program implementation. This increase is supported by qualitative data showing improved student activity (reaching 80% in the presentation session) and the strengthening of cultural identity. The program successfully established an innovative, relevant, and contextual learning model, and enhanced teacher competence in integrating local wisdom.